Luminosity determination in pp collisions at √s = 8 TeV using the ATLAS detector at the LHC - Onofre, A. (2016)
The luminosity determination for the ATLAS detector at the LHC during pp collisions at √s= 8 TeV in 2012 is presented. The evaluation of the luminosity scale is performed using several luminometers, and comparisons between these luminosity detectors are made to assess the accuracy, consistency and long-term stability of the results. A luminosity uncertainty of δL/L=±1.9% is obtained for the 22.7fb−1 of pp collision data delivered to ATLAS at √s= 8 TeV in 2012.